1989
DOI: 10.1192/bjp.155.6.829
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Related Behaviour from River Bridges

Abstract: A survey was conducted of 47 suicides, 16 failed suicides, and 24 attempted suicides that occurred from Brisbane river bridges over 15 years. Compared with findings from other suicide surveys, subjects of bridge suicides and failed suicides had a much higher rate of schizophrenia (46%), with hallucinations often precipitating the jump. They also had extensive histories of previous self-harm. Those who attempted suicide by jumping had a higher rate of personality disorder (58%) compared with findings from other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
2
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 21 publications
(1 reference statement)
5
47
2
3
Order By: Relevance
“…In such cases, auditory hallucinations, for example, can influence the decision to commit suicide in a specific manner. It should be pointed out that among the suicides by all other means put together, the percentage of psychotic individuals is usually no way as high as in this group (Cantor et al, 1989). However, at least one study by Nowers and Gunnell (1996) found that those jumping from the Clifton Suspension Bridge in England were no more likely to have psychiatric histories and have been psychiatric inpatients than matched controls using other suicide methods.…”
Section: Preference For a Particular Means Of Committing Suicidementioning
confidence: 95%
“…In such cases, auditory hallucinations, for example, can influence the decision to commit suicide in a specific manner. It should be pointed out that among the suicides by all other means put together, the percentage of psychotic individuals is usually no way as high as in this group (Cantor et al, 1989). However, at least one study by Nowers and Gunnell (1996) found that those jumping from the Clifton Suspension Bridge in England were no more likely to have psychiatric histories and have been psychiatric inpatients than matched controls using other suicide methods.…”
Section: Preference For a Particular Means Of Committing Suicidementioning
confidence: 95%
“…Previous Australian studies have found that schizophrenia and personality disorder were prominent in self-harm by jumping from bridges. 2,15 Two other studies of ASCI after self-harm report few characteristics of the study populations and have no long-term follow-up. 16,17 Schizophrenia is a low-prevalence disorder and the Australian point prevalence is reported as 4.7 per 1000 in urban populations between the ages of 18 and 64 years.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, during the 1980s there was an increase in suicide by jumping in Australia, the UK, Switzerland and Finland. 2,3 We speculated that the incidence of self-harm resulting in spinal cord injury (largely by jumping) might have been influenced by deinstitutionalisation of psychiatric care and the use of recreational drugs. Deinstitutionalization of Australian psychiatric facilities occurred from the 1960s to 1980s 6 possibly leading to lower levels of supervision, poor treatment compliance and increased risk of deliberate self-harm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les données de la littérature regroupant l'ensemble des cas de précipitation mentionnent en général une prédominance de patients présentant des psychopathologies sévères (schizophrénie, maladie dépressive majeure) [8][9][10][11]. Cependant, certains auteurs n'ont trouvé aucune différence entre les groupes de suicidants quant à leur psychopathologie [12].…”
Section: Discussion Epidémiologieunclassified